A cargo of lead ingots from a shipwreck off Ashkelon, Israel 11th–13th centuries AD. (7th August 2019) - Galili, Ehud; Rosen, Baruch; Arenson, Sarah; Nir‐El, Yoram; Jacoby, David
Abstract: Shipwreck cargo of lead ingots, some marked, discovered off Tel Ashkelon, weighed about four tonnes. C14 analysis of charred wood from an ingot dated it to the 11th–13th centuries AD, Crusader times. Lead isotopic ratios provenanced the ingots to Mont‐Lozère, France. Various aspects of the lead trade are discussed, including: lead sources, extraction, casting, lead in the international maritime trade, weight units in medieval trade, prices, transportation, sale and storage, lead cargo and ballast, reconstruction of the wrecking event, salvage after the vessel was wrecked, Ashkelon as a trading coastal town in the 11th–13th centuries AD, and the possible destination of the cargo. Abstracto: Una carga de lingotes de plomo de un naufragio en Ascalón, Israel (Siglos XI – XIII d.C.) Una carga de lingotes de plomo ‐ algunos marcados – descubierta en Tel Ascalón, pesó alrededor de cuatro toneladas. El análisis de carbono 14 de maderas carbonizadas halladas en un lingote arrojó una fecha de los siglos XI al XIII d.C., época de las Cruzadas. Las tasas isotópicas permitieron determinar que los lingotes provenían de Mont‐Lozère en Francia. Se discuten varios aspectos del comercio de plomo que incluyen: las fuentes de plomo, la extracción, el moldeado, el plomo en el comercio internacional marítimo, unidades de medida de peso en el comercio medieval, precios, transporte, venta y almacenamiento, carga de plomo y lastrado, reconstrucción del evento del naufragio, salvamento tras el naufragio, Ascalón como pueblo costero comercial en los siglos XI al XIII d.C. y el posible destino de la carga. 抽象: 以色列亚实基伦海域一艘沉船中公元11‐13世纪的铅锭 在亚实基伦遗丘附近海域发现的铅锭船货, 重约4吨, 其中一些带有标记。对附着在一块铅锭上的焦木的碳14分析确定其年代在十字军东征时代, 即公元11至13世纪。铅同位素比值证明了这些铅锭来源于法国的洛泽尔峰地区。本文探讨了铅贸易的诸多方面, 包括铅来源、提炼、铸造, 国际海运贸易中的铅、作为中世纪贸易的重量单位的铅及其价格、运输、销售和储存, 铅货和压舱物, 重建船只沉没过程及对沉船的打捞, 11至13世纪作为沿海贸易城镇的亚实基伦以及船货的可能目的地。 以色列亞實基倫海域一艘沉船中公元11‐13世紀的鉛錠 在亞實基倫遺丘附近海域發現的鉛錠船貨, 重約4噸, 其中一些帶有標記。對附著在一塊鉛錠上的焦木的碳14分析確定其年代在十字軍東征時代, 即公元11至13世紀。鉛同位素比值證明了這些鉛錠來源于法國的洛澤爾峰地區。本文探討了鉛貿易的諸多方面, 包括鉛來源、提煉、鑄造, 國際海運貿易中的鉛、作爲中世紀貿易的重量單位的鉛及其價格、運輸、銷售和儲存, 鉛貨和壓艙物, 重建船只沉沒過程及對沉船的打撈, 11至13世紀作爲沿海貿易城鎮的亞實基倫以及船貨的可能目的地。 ملخص: